Analysis of Renewable Energy, Environment Quality and Energy Consumption on Economic Growth: Evidence from Developing Countries - Satrianto, Alpon; Ikhsan, Akmil; Samad, Khairunnisa Abd (International Journal of Energy Economics and Policy, 2024)
The stage of economic development of a country will have an impact on the essence of life in welcoming changes in the economic pattern in the future. Especially in the energy sector, currently almost all countries are actively trying to achieve an energy transition to support the sustainability of a clean and orderly environment. Therefore, this research focuses renewable energy, environmental quality and energy consumption on economic growth in 30 developing countries using panel data model with a Fixed Effects Approach. The results show that renewable energy and environmental quality variables contribute significantly to economic growth, while energy consumption does not have a significant effect. At this stage, facilities for developing renewable energy must be expanded in terms of infrastructure capacity and financing so that they are supported by government policy. Then, macroeconomic variables such as foreign direct investment and population have a significant effect on economic growth, while trade oppenes and labor force variables do not have a significant effect on economic growth in developing countries, adding to the indication and reference of the importance of balance in achieving the energy transition and macroeconomic policies that have an impact on progress economy.